Effectiveness of Online Harmonization Facilitation Services for Regional Regulation Drafts - Andra, Aman; Putri, Nora Eka (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study examines the online Harmonization Facilitation Services of Draft Regional Regulations (Legal Sector) in 2020-2021 at West Sumatra's Ministry of Law and Human Rights. The research method is descriptive qualitative, and the results indicate that the implementation of harmonization in 2020 was delayed, leading to an entirely online approach. In 2021, hybrid harmonization will be done using WhatApps and the E-Perda Rancak application. The integration aspect of harmonization is carried out online, using WhatApps and the E-Perda Rancak application. The implementation of harmonization of draft local regulations online has led to changes that do not align with objectives. The socialization of harmonization policies in 2021 will be conducted hybrid, involving coordination meetings with the central and local governments. This does not significantly contribute to harmonization, starting from the application procedure to the harmonization meeting of the draft local regulations. The adaptation aspect of online harmonization in 2020-2021 can be adjusted through efforts in human resources, facilities, and infrastructure preparations for the office and parties involved. Coordinating meetings with central and regional governments have contributed significantly to harmonization, from the submission procedure to the harmonization meeting of the draft local regulations.